Analysis of Factors Contributing to Treatment Success among Tuberculosis Patients: Cross-Sectional Study in Semarang, Indonesia - Nur Dian Rakhmawati; Muhamad Zakki Saefurrohim; Warsono Warsono (Universitas Muhammadiyah Semarang, 2023)
The success rate of TB treatment in Semarang City in 2021 will reach 81.15%. Patients recovered reached 20.20%. Complete Treatment reached 60.95%. Failed treatment 0.15%. Patients Died reached 5.96%. Treatment dropout (lost to follow-up) reached 12.43%. Not evaluated/moved reached 0.31%. This study aims to identify the factors that contribute to the success of TB treatment. This study used secondary data sourced from the Semarang City Tuberculosis Information System (SITB) which was recorded regularly during 2021-2022. 4,627 TB patients who had minimally complete variables were entered into univariate analysis, crosstabulation and binary logistic regression. The results of the multivariate analysis showed a joint relationship between the factors that contributed to the success of TB treatment. Negative DM Status (AOR = 1.33; CI95% = 1.092-1.619), Standard Treatment Status (AOR = 1.767; CI95% = 1.235-2.529), Type Puskesmas Health Facility (AOR=3.778; CI95%=3.114-4.582), New Patients Based on Previous Treatment History (AOR = 1.592; 95% CI = 1.263-2.007) with Nagelkerke R Square = 13.2%. TB treatment success strategies in Semarang City need to be improved.